Leiomyosarcoma of the Oropharynx and Neurogenic Tumors in a Young Patient With Turner's Syndrome. (2001) - De Chiara, Annarosaria; Apice, Gaetano; Silvestro, Giustino; Losito, Simona; Botti, Gerardo; Ionna, Francesco; De Rosa, Vincenzo; Borghese, Annamaria; Ninfo, Vito
Abstract : Patient: A case of Turner's syndrome developing a leiomyosarcoma of the oropharynx and metachronous neurogenic tumors (mediastinal 'ganglioneuroblastoma intermixed', subcutaneous neurilemoma) is described. Discussion: To our knowledge, this case is the second reported leiomyosarcoma in a patient with Turner's syndrome. Also the site of involvement (palate and oropharynx) is particularly unusual for the already rare leiomyosarcomas in the young age.